Artificial aging route for assessing the potential efficacy of consolidation treatments applied to porous carbonate stones. (15th April 2017) - Sena da Fonseca, B.; Ferreira Pinto, A.P.; Piçarra, S.; Montemor, M.F.
Abstract: Unsatisfactory behaviors of consolidation treatments applied to porous carbonate stones in the field are frequent, although they had revealed promising performances when applied to sound stones in laboratory. Thus, accurate assessment of the potential efficacy of consolidation treatments in laboratory conditions is of outmost importance to support conservation practice. This paper compares heating and freeze-thaw as artificial aging procedures for testing consolidants on a selected porous carbonate stone (CaCO3  ≈ 99.9%, porosity = 16% and average pore radius = 0.4 μm). The induced decay was assessed by physical tests and drilling resistance measurement system (DRMS), which is a well-establish method to characterize materials and evaluate the efficacy of consolidation treatments. Heating caused minor alterations, because the anisotropic thermal expansion of calcite was compensated by the stone porosity, whereas the freeze-thaw cycles produced important alterations. Sound and pre-aged specimens by freeze-thaw were treated with different alkoxysilane-based consolidants and their effect on the mechanical properties was assessed by DRMS and analyzed using the difference drilling profile method (DDP). The obtained results highlighted the interest of using pre-aged specimens by freeze-thaw and the usefulness of the procedures adopted for the assessment of the potential efficacy of consolidation treatments applied to porous carbonate stones. Graphical abstract: Highlights: Aging by heating causes none or minor damage in the used porous carbonate stone; Freeze-thaw cycles induce significant physical and mechanical modifications in the used porous carbonate stone; Drilling resistance is an important tool for the characterization of mechanical damage induced by aging procedures; A promising procedure to study the potential efficacy of consolidants in artificially aged porous carbonate stones was used.